Ukraine : Technical Assistance Report-Reforming the State Fiscal Services. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses State Fiscal Service (SFS) Reform of Ukraine and a plan of action. This mission is a follow-up to the Fiscal Affairs Department (FAD) mission of July 2014 and has focused on the recently adopted reform plan for revenue administration in the SFS. In 2015, the revenue performance has met expectations for the major taxes. There are concerns that amounts for corporate income tax (CIT) advance payments and value-added tax refunds will erode future performance. Advance payments of CIT have not been credited against tax assessments. The 2014 FAD mission made a number of recommendations aimed at short-term revenue improvement before long-term institutional changes were adopted.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet